Results from SYNTAX - Vinall, Maria (MD Conference Express, 2009)
This article discusses the 2-year results from the SYNTAX study [NCT00114972], suggesting that coronary artery bypass grafts may be more appropriate for patients with complex three-vessel and/or left main coronary disease, while percutaneous coronary intervention may be an acceptable alternative for patients with less complex disease.